"In Eight Minutes We Talked More About Our Goals, Relationship, Than We Have in Years": A Pilot of Patient–Caregiver Discussions in a Neuro-Oncology Clinic. (May 2020) - Ketcher, Dana; Ellington, Lee; Baucom, Brian R. W.; Clayton, Margaret F.; Reblin, Maija
Primary brain cancer is a diagnosis that can have drastic health impacts on patient and caregiver alike. In high-stress situations, dyadic coping can improve psychosocial and health outcomes and communication about personal life goals maybe one way to facilitate this coping. In this study, we describe the feasibility and accessibility of a one-time, self-directed goal discussion pilot intervention for neuro-oncology patients and their primary caregivers. Ten dyads were taken to a private room to complete a pre-discussion questionnaire, a worksheet to elicit personal goals, complete an 8-min discussion of goals, a post-discussion questionnaire, and provided open-ended feedback about the process. Post-discussion, dyads reported that the intervention was not stressful. In open-ended feedback, dyads overwhelmingly reported that the intervention was a positive experience, providing a safe, calm environment to have difficult conversations. This intervention provides a positive framework for improving communication and discussion of goals between patient–caregiver dyads.